Rekonstruksi Evaluasi Pembelajaran Perspektif Islam Berbasis Afektif: Indonesia - Akh.Bayu Rifki; Man Arafah; Ismail Thoib; Nurhilaliati (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2024)
This study focuses on how the Islamic view of reconstructing the educational evaluation method affects the affective aspect (attitude). The purpose and function of this evaluation are to measure not only academic achievement but also the development of students' character and morals in accordance with Islamic values. The research methods used include literature studies (library research). The results of this study begin by understanding the meaning of evaluation in Islamic education and the underlying principles. Furthermore, an affective-based research model that prioritizes the evaluation of students' attitudes, values, and ethics is described. The concept of educational evaluation from an affective Islamic perspective was then developed to provide a more holistic framework. This research shows that this approach can increase emotional and spiritual engagement, as well as support the internalization of Islamic values in daily life. The implications of this study emphasize the need for effective evaluation ideas and training for educators in implementing affective based evaluation. Keywords: Reconstruction, Evaluation, Islamic Education, Affective